Kajian Ragam Aksesi Duku (Lansium domesticum Corr.) di Kabupaten Musi Banyuasin Berdasarkan Karakter Morfologi, Anatomi dan Fisiologi - Dr. Susilawati Susilawati (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2016)
Susilawati et al, 2016. Study Variaty of Duku Accession (Lansium domesticum Corr.) in Musi Banyuasin Regency Based on Morphology, Anatomy and Physiology Characters. JLSO 5(1):105-118. One duku production center in South Sumatra is Musi Banyuasin. The aims of this research was to know character of  morphology, anatomy and physiology of duku accession (Lansium domesticum Corr.) in Musi Banyuasin Regency. This research was carried out on February until April 2016 in Musi Banyuasin regency. The method being used was direct observation and survay. The Observations took on quantitative and qualitative characters included morphology, anatomy and physiology characters. The results analyzed by comparing diversity of phenotypic variance and standard deviation values. Genetic relationship determined using cluster of program-pc NTSYS 2:02 by clustering analysis. The result of research showed duku in Musi Banyuasin has a diversity phenotypes of quantitative and similarity qualitative characters except the color of leaves. The level of duku diversity in Musi Banyuasin  was 48% with similarity rate 75%.